Review of: Lebedev E. E., Rodionov V. G., Semenova I. P., Kasimov E. V. N. I. Ashmarin - the coryphaeus of Chuvash philology. Cheboksary: Chuvash book publishing house, 2020. 270 p - Eduard V. Fomin (Publishing house "Sreda", 2023)
Review, abstract, keywords.